2004
DOI: 10.1161/01.atv.0000142376.30582.ed
|View full text |Cite
|
Sign up to set email alerts
|

ADP Receptor P2Y 12 Is Expressed in Vascular Smooth Muscle Cells and Stimulates Contraction in Human Blood Vessels

Abstract: Objective-ADP plays an important role in platelet aggregation by activating P2Y 12 receptors. We assessed the hypothesis that P2Y 12 receptors are expressed in vascular smooth muscle cells (VSMC). Methods and Results-P2Y 12 receptor mRNA was found to have a high expression among the P2 receptors in human VSMC, significantly higher than the other 2 ADP receptors (P2Y 1 and P2Y 13 , real-time polymerase chain reaction). Western blots gave a band of 50 kD, similar to that in platelets. To unmask a P2Y 12 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(152 citation statements)
references
References 25 publications
9
138
1
4
Order By: Relevance
“…Although most relevant studies have highlighted the relative specificity of brain P2RY12 expression to microglial cells, some controversy on the point exists, in that studies have variably reported that P2RY12 might also be expressed in brain endothelial cells (35), human smooth muscle vascular cells (36), and astrocytes (37). However, these reports have without exception been based on analysis of cultured cells or ex vivo preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Although most relevant studies have highlighted the relative specificity of brain P2RY12 expression to microglial cells, some controversy on the point exists, in that studies have variably reported that P2RY12 might also be expressed in brain endothelial cells (35), human smooth muscle vascular cells (36), and astrocytes (37). However, these reports have without exception been based on analysis of cultured cells or ex vivo preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that the P2Y12 receptor is expressed not only in platelets but also in other cell types, such as monocytes (122), VSMCs (123), dendritic cells (124), and lymphocytes (122). Therefore effects of ADP-antagonists are not only expected in platelets but also in the target cells mentioned above.…”
Section: Platelets Inflammation and Antiinflammatory Drugs In Acs Anmentioning
confidence: 99%
“…[17,18] These receptors have also been found to exist in cells other than platelets, including the rat and human vascular smooth muscle cells. [19] Adenosine diphosphate has been shown to induce vasoconstriction via P2Y12 receptors; however, it is also believed to cause arterial relaxation by increasing the synthesis of endothelium-derived nitric oxide (NO). [19][20][21] Thus, the effect of ADP-mediated pathways on the endothelium is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Adenosine diphosphate has been shown to induce vasoconstriction via P2Y12 receptors; however, it is also believed to cause arterial relaxation by increasing the synthesis of endothelium-derived nitric oxide (NO). [19][20][21] Thus, the effect of ADP-mediated pathways on the endothelium is currently unclear. [22] Clopidogrel has been reported to exhibit vasomodulatory activity [23] and direct endothelial effects independent from antiplatelet actions, [24] which are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%